NURSES’ AWARENESS, CONCERN, MOTIVATION, AND BEHAVIOR TOWARD HEALTH AND CLIMATE CHANGE - Manik, Marisa Junianti; Agustin, Angel; Immanuel, Chandra; Putri, Retno Pramita; Sihaloho, Shinta M.J.P. (Nursing Current: Jurnal Keperawatan, 2024)
Climate change significantly impacts health, food security, housing, safety, and work through long-term shifts in temperature and weather patterns. In Jakarta, these changes have led to the city experiencing the worst air pollution in Indonesia, with an Air Quality Index (AQI) score of 161. Nurses play a vital role in educating the public about behavioral changes to mitigate the effects of climate change. This study aimed to assess nurses' awareness, concerns, motivation, and behaviors related to health and climate change in a private hospital in Jakarta. This quantitative descriptive study involved 92 respondents selected through purposive sampling. The data were collected using the Climate, Health, and Nursing Tool (CHANT) questionnaire. The analysis revealed that nurses' awareness of evidence-based information on climate change ranged from "somewhat familiar" to "moderately familiar." Their concerns about the impacts of climate change were rated from "somewhat concerned" to "moderately concerned." Nurses' motivation levels were reported as ranging from "somewhat motivated" to "very motivated" regarding health and climate change. Behavioral practices to mitigate climate change varied, with activities at home ranging from "rarely" to "often" and those in the hospital ranging from "sometimes" to "often." This research highlights the need to enhance nurses' knowledge and awareness of health and climate change and serves as a reference for future studies exploring the intersection of nursing, health, and climate change in Indonesia.